2016
DOI: 10.1007/s13721-016-0131-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene co-expression network analysis reveals common system-level properties of genes involved in tuberculosis across independent gene expression studies

Abstract: Network-based approaches to human disease have diverse biological and clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recent computational methods of systems biology, including network analysis and machine learning, are suitable for analyzing omics techniques such as high throughput RNA-sequencing (RNA-seq) at the systemic level (18). Weighted gene coexpression network analysis (WGCNA) is a systems biology method to identify clusters (modules) of highly correlated genes, candidate biomarkers, and therapeutic targets (19); it has been used in various human infectious diseases, e.g., Influenza (20), Tuberculosis (21,22), Hepatitis B,C (23)(24)(25), HIV (26), and various cancers (27)(28)(29)(30). Additionally, in some studies using the module-trait relationships approach of WGCNA, modules related to clinical traits of COVID-19 were identified at various stages (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Recent computational methods of systems biology, including network analysis and machine learning, are suitable for analyzing omics techniques such as high throughput RNA-sequencing (RNA-seq) at the systemic level (18). Weighted gene coexpression network analysis (WGCNA) is a systems biology method to identify clusters (modules) of highly correlated genes, candidate biomarkers, and therapeutic targets (19); it has been used in various human infectious diseases, e.g., Influenza (20), Tuberculosis (21,22), Hepatitis B,C (23)(24)(25), HIV (26), and various cancers (27)(28)(29)(30). Additionally, in some studies using the module-trait relationships approach of WGCNA, modules related to clinical traits of COVID-19 were identified at various stages (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…liu et al (16) also reported that the glucose-6-phosphate dehydrogenase and S100 calcium binding protein a7 genes may represent potential targets in coronary artery disease (16). in a further study, WGCNA identified seven modules that are notably linked with latent and active tuberculosis (17). Therefore, WGcna may be applied to analyze microarray data for colon cancer.…”
Section: Introductionmentioning
confidence: 95%